(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2025)
The following article demonstrates the evolution of the mask within Mexican society, where it passes from being an exclusive object of rituals and traditions to its sale as a simple object of decoration and consumption; between these two poles is the mask as part of the representation of the sport and the character to the world, being an object that represents the good use of the object in these two poles. The study of the evolution and appearance of the mask of the fighter within the historical can be analyzed through the change in materials for its construction and the meaning behind its use and imitation of the world around it. Evolution does not mean the disappearance of one pole over another; it is rather the adaptation of the religious object to social transformation for the survival of culture as a craft work.